Cities in Global Transition: Creating Sustainable Communities in Australia - Rauscher, Raymond Charles; Momtaz, Salim (Springer International Publishing AG, 2016)
This book examines the planning of cities in global transition, looking at Australia's Greater Sydney as a case example. The focus is on metropolitan districts (groups of municipalities) within the Greater Sydney region. The subjects of global transition and sustainable urban planning (SUP) are introduced in Chapter 1. How Greater Sydney approaches planning of its region and its districts is then outlined in Chapter 2. In this chapter, three case study districts are selected for critiquing planning in the face of population and new development changes. The districts, beyond the City of Sydney, are: Sydney Inner West, Greater Parramatta and St George. The book further outlines a methodology to assess planning practices within each of the municipalities (twelve case study municipalities in all within the three districts). Included here are State planning principles applying to Greater Sydney, with key principals selected to apply to the case study municipalities and to each district as a unit.